Design of a Chemical Literacy Test Instrument on Atomic Structure Material for Senior High School Students - Siti Faizah; Yerimadesi Yerimadesi; Nofri Yuhelman; Iryani Iryani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The low level of chemical literacy in Indonesia, reflected in PISA 2022 scores below the average, is driven by the limited use of literacy-based assessments and restricted access to proper evaluation instruments. This study aims to develop and validate a chemical literacy test instrument specifically designed for atomic structure material for Senior high School students, utilizing the Rasch model for rigorous psychometric analysis. Unlike previous studies that often integrate multiple chemistry topics, this research provides a specialized focus exclusively on atomic structure, featuring five contextual narratives and one infographic across seven essay items to capture deep conceptual understanding. This Research and Development (R&D) employed purposive sampling of students at SMA N 7 Padang. Data were analyzed using Content Validity Ratio (CVR) for logical validity and Rasch modelling via Ministep software for empirical validation. The Rasch model was selected over classical test theory to ensure linear measurement of both item difficulty and student ability. SME evaluations confirmed the logical validity of all items. Empirical analysis showed that although some items exhibited higher outfit values, they were retained because of strong point-measure correlations with the measured construct. Item reliability was categorized as good, person reliability as fair, and Cronbach’s alpha was categorized as good. The instrument effectively categorized item difficulty and student discrimination power into three ability levels (high, medium, and low). The resulting seven-item instrument is valid, reliable, and practically feasible for educators to integrate into formative assessments to measure students' chemical literacy in atomic structure.